Overexpression of PdC3H17 Confers Tolerance to Drought Stress Depending on Its CCCH Domain in Populus - Zhuang, Yamei; Wang, Congpeng; Zhang, Yang; Chen, Sihui; Wang, Dian; Liu, Qing; Zhou, Gongke; Chai, Guohua (Frontiers in Plant Science, 2020)
Plant CCCH zinc finger proteins control growth, development and stress responses mainly at the post-transcriptional level. Currently, limited reports are available about the roles of plant CCCH proteins in drought tolerance. In this study, we provided evidence showing that PdC3H17 from Populus deltoides × P. euramericana’ involves drought tolerance and response. Overexpression of PdC3H17 in poplar caused dwarf, resulted in higher stem water potential, and showed increased photosynthetic and ROS-scavenging abilities, thereby enhancing tolerance to drought stress, compared to controls. Accordingly, after drought treatment the stem elongation and thickening rates of these overexpression lines were higher than those of the controls. However, overexpression of the coding region excluding the CCCH domain of PdC3H17 roughly exhibited WT-like physiological and drought-resistant phenotypes, indicating the requirement of the CCCH domain for PdC3H17 controlling these processes. In addition, N-terminal sequence of PdC3H17 was found to possess transcriptional activity ability in yeast cells. Together, our results suggest that PdC3H17 may depend on its CCCH domain to control drought tolerance in Populus.